The Relationship between School Culture and Social Climate Governing School with Academic Ethics and the Mediating role of learners’ Academic - Langari, Reza; Soleimanpouromran, Mahboubeh (Iranian Journal of Educational Sociology, 2022)
Purpose: This research was conducted with the aim of studying the relationship between school culture and social climate governing school with academic ethics and mediating role of educational buoyancy.Methodology: The present study is descriptive, cross-sectional, purposeful, applied, and essentially a descriptive survey. It has been surveyed by a questionnaire. The statistical population of the study was all boys' high school students in Bojnourd city who were 5172 people. Of these, 382 were selected by relative sampling according to the Morgan table for participation in the research. The research tools consisted of Alessandro and Sadh School Culture (1997), Social Psychosocial Class Questionnaire (Frazer, Giddings and McBurby, 1995), Educational Buoyancy Questionnaire (Hossein Chari and Dehghanizadeh, 2012), and Educational Ethics Questionnaire (Golparvar, 2010). The validity of the instrument was of formal and content type, while its reliability calculated by Cronbach's alpha coefficient for school culture questionnaire turned out to be 0.939, Psycho-social 0.84, academic buoyancy 0.837 and academic ethics 0.869. Data were collected from questionnaires using descriptive statistics (frequency distribution, mean, standard deviation and calculation of central indicators and dispersion); to find the results of the research hypotheses, inferential tests including multiple regression analysis was employed using SPSS software (version 19). Also to test the validity of the theoretical model and calculate the effect coefficients Structural Equation Modeling Method with Lisrel 8.8 software was used.Findings: The results showed that there is a relationship between school culture and social climate governing school with students' academic ethics. There is also a relationship between school culture and students' academic buoyancy. Also, academic buoyancy has a mediator role in relation to school culture and students' academic ethics (p> 0.05).Conclusion: The findings show that there is a relationship between school culture and students’ educational ethics, so by upgrading and strengthening school culture, students' academic ethos will be consolidated. Also, school culture has a positive and significant effect on the basic psychological needs of autonomy, competence and communication.